Toxicity of nano-emulsion formulation of azadirachtin against Tribolium castaneum (Herbst) & Sitophilus oryzae (L.) - Choupanian, Marziyeh (2016)
Sitophilus oryzae and Tribolium castaneum are known as the most destructive and cosmopolitan pests which can cause a huge damage on most of common stored products annually. Massive use of synthetic pesticides has created serious problems such as hazards to the environment, residues in foodstuffs, and development of resistant strains. Plant-derived products could be the alternative to control the pests for many reasons such as being eco-friendly, residue-free, biodegradable and cost-effective. Neem oil is one of the plant-based pesticides comprises of azadirachtin as active ingredient. It has been used extensively against an array of pest species. Nonetheless, the problem with neem oil is the low stability of azadirachtin molecule due mainly to photo-degradation. Recently, emulsion-based formulations have gained immense interest due to their green characteristics, wide range of potential and utilization. Thus, this study was conducted to develop nano-emulsion formulations of neem oil with improved stability and toxicity against S. oryzae and T. castaneum. The nano-emulsion formulations were developed by constructing ternary phase diagrams, and four formulations coded as NF1, NF2, NF3 and NF4 were selected from the isotropic regions. All the selected formulations were miscible with neem oil and comprised of either nonionic polysorbate (Tween 80) or alkylpolyglucoside (MBL 510H) surfactant. NF1 and NF2 contained MBL510H, while NF3 and NF4 contained Tween80. All the selected formulations were stable under centrifugation and storage at ambient temperature of 25°C. However, NF2 showed phase separation at 54°C after 14 days storage and transformed to two opaque phases. The results of the mean particle size of the selected formulations showed the droplet size ranging between 200-600 nm, which can be considered as nano-emulsion formulation. The smallest droplet sizes were obtained from the NF3 and NF4 with Tween80 as surfactant. The zeta potential and surface tension of the formulations ranged between 31 to 39 mV and 30.52 to 33.33 mNm-1. The results also indicated viscosity and pH of the nano-emulsion formulations ranging 65 to 88 Pa.s, and 3 to 5, respectively. The toxicity of the nano-emulsion formulations against the adults of S. oryzae and T. castaneum were evaluated using filter paper impregnation method and food impregnation method. Neem oil and commercial EC formulation of azadirachtin (Neemix®) were used as positive control. The results showed the interaction between formulations and concentrations of azadirachtin. The higher the concentration of a formulation results in increased of the mortality. The toxicity of the formulations against both insects for both methods in increasing order was NF3≥ NF4> NF1≥ NF2>Neemix> Neem oil at 24 h after exposure. The NF3 was found to be the most toxic formulation with 58.25 and 43.5% mortality against S. oryzae and T. castaneum, respectively, via food impregnation method and after 24 h of exposure. However, lower mortality of 25.25% and 21% against S. oryzae and T. castaneum, respectively, of the filter paper impregnation method were obtained. This result indicated that the food impregnation method is more effective to control both insects. The rate of mortality as indicated by the LT50 value of 9.61 h and 11.27 h against S. oryzae and T. castaneum, respectively, at 1% concentration of the NF3 for the food impregnation method was the fastest among the formulations tested. Similar trend for the NF3 was obtained for the filter paper impregnation method with LT50 values of 17.01 h and 19.26 h against S. oryzae and T. castaneum, respectively. This could be due to the smaller particle size of the formulation. Polysorbate surfactant is more efficient in comparison with alkylpolyglucoside surfactant due to the higher mortality of the NF3 and NF4 on both insects. The results revealed significant increase of mortality from the nano-emulsion formulations. There is therefore immense potential for development of neem oil from these nano-emulsion formulations.